Pengaruh Integrative Behavioral Couple Therapy terhadap Pola Asuh Coparenting Orangtua - Khair, Nurul Fadhilah (ANFUSINA: Journal of Psychology, 2020)
Parents play an important role in the family, while the second role plays in parenting is very much needed by the child's development. Child's psychological development will be much better, if both require joint care or coparenting. The pattern of joint care or coparenting is mutual support and act as a team of mutual support, which is carried out by both parties. The main concept of coparenting care here is second, interconnected or mutually supportive in all forms of attitudes, relationships and teaching in parenting practices. This study uses a single case study design with A-B-A model in which this research method is deemed suitable for the assessment of changes in therapy and applied therapy in couples. The results of the study showed a change in coparenting scores in each pair.